The Synthesis of Hexafluorosumanene and Its Congeners. Issue 10 (10th February 2013) - Schmidt, Bernd M.; Topolinski, Berit; Higashibayashi, Shuhei; Kojima, Tatsuhiro; Kawano, Masaki; Lentz, Dieter; Sakurai, Hidehiro
Abstract : Bowled over : A family of gem ‐difluorinated sumanenes was synthesised, including the highly symmetric hexafluorosumanene (see figure). The favourable columnar structure is maintained upon fluorination. Substitution by electron‐withdrawing substituents increases the bowl depth and results in a large cathodic shift of the reduction potential.